Reframing corporate social responsibility lessons from the global financial crisis - Sun, William, 1962-; Stewart, Jim, 1952-; Pollard, David, 1946- (Emerald, 2010)
Most of people have believed that corporate social responsibility (CSR) played a significant role in the 2008 global financial crisis. However, little research has been done to reflect on the underlying issues of CSR in connection to the financial crisis. This collection brings together leading scholarly thinking to understand why CSR failed to prevent the global financial crisis, how corporate social irresponsibility (CSI) contributed to the financial crisis, and how we may reframe CSR or improve CSR frameworks to help prevent or mitigate any future financial and economic crises. While the conventional CSR theories are identified as an implicit construction of alienated CSR, a new perspective of CSR, namely, an embedded CSR, is proposed in this volume. CSR involves a variety of issues and demands continuing and multidisciplinary explorations. As a pioneering research into embedded CSR, this volume concentrates on three key themes: A critical review of the role of CSR played in the financial crisis and its underlying theses; A unique understanding of the institutionalization of CSR in codified rules and the application of CSR into business and management; and An in-depth exploration of the future direction of CSR as post-crisis agenda.
Keywords: Social responsibility of business.; elektronické knihy; electronic books